Analysis of the Influence of the Paok Motong Tobacco Factory Agglomeration (APHT) on the Level of Employment Opportunities in East Lombok Regency - R. Bimo Ario Tejo; Busaini Busaini; Siti Fatimah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This research aims to analyze the influence of production capacity, number of industrial workers, production productivity, and prices of tobacco raw materials on the level of employment opportunities in East Lombok Regency in the Paok Motong Tobacco Factory Agglomeration (APHT) area. This research uses a quantitative approach with explanatory research. The data used is time series data for the period 2023–2025 obtained from the Central Statistics Agency (BPS), KPPBC TMP C Mataram, and field observations. The data analysis technique uses multiple linear regression with the help of the EViews application. Before regression analysis is carried out, the model is tested using classic assumption tests including normality, multicollinearity, heteroscedasticity and autocorrelation tests to ensure the model meets the Best Linear Unbiased Estimator (BLUE) criteria. The research results show that production capacity has a negative but not significant effect on the level of employment opportunities. This condition shows that increasing production capacity is achieved more through operational efficiency than adding new workers. Meanwhile, the number of industrial workers, production efficiency and the price of tobacco raw materials have a positive and significant effect on the level of employment opportunities in East Lombok Regency. Simultaneously, all independent variables have a significant effect on the level of labor absorption. Research findings show that the presence of the APHT Paok Motong area makes a significant contribution to employment opportunities and regional economic development. Therefore, local governments need to encourage the development of labor-intensive industries, improve workforce skills, and stabilize the supply of raw materials to increase employment opportunities in a sustainable manner.